An Analysis of Students in Pronouncing English Fricative at The English Department of Unida Gontor - Diska Fatima Virgiyanti; Nurin Farzana; Dinar Dipta; Aries Fachriza; Eka Indah Nuraini (Universitas Muhammadiyah Jember, 2025)
This research aims to investigate the types and factors of students’ errors in pronouncing interdental and alveolar fricative sounds. The methodology of this research used descriptive qualitative with percentages. Interview guidance included a pronunciation test, questionnaire, and documentation utilized in this research as instruments. 7 out of 37 respondents were selected by purposive random sampling for the interview. Data analysis used three stages such as error identification, classification error, and explanation error. Then, to validate data used data triangulation. The result of this study revealed that students had deviation in all types of errors. Namely, the misformation of 1525 scores, the addition of 113 scores, the omission of 80 scores, and the misordering of 26 scores. All respondents obtained a moderate classification of pronunciation errors and the sound /θ/ of 79%, the sound /ð/ of 81%, and the sound /z/ of 84% included a high error percentage classification. Lastly, Students’ pronunciation errors are influenced by 3 categories of error sources, namely interlingual transfer, intralingual transfer, and context of learning.